Learning as a family every day (4) (Journal of Parents and Teachers, 1996)
The article analyzes the work of Tintin and his creator, Hergé, highlighting the combination of images and dialogues in the visual narrative. Tintin, introduced in 1930, becomes a defender of just causes, while characters such as Captain Haddock add complexity to the story. The work reflects values of sincerity and adventure, with a focus on exploration and social criticism.
Keywords: visual storytelling; just causes; social critique; exploration